2004
DOI: 10.1007/s00424-004-1320-3
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandins and nitric oxide in regional kidney blood flow responses to renal nerve stimulation

Abstract: We examined the roles of cyclooxygenase products and of interactions between the cyclooxygenase and nitric oxide systems in the mechanisms underlying the relative insensitivity of medullary perfusion to renal nerve stimulation (RNS) in anaesthetized rabbits. To this end we examined the effects of ibuprofen and N(G)-nitro-L: -arginine (L-NNA), both alone and in combination, on the responses of regional kidney perfusion to RNS. Under control conditions, RNS produced frequency-dependent reductions in total renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
5
8
0
1
Order By: Relevance
“…Thus this decrease in MAP results from decreased vascular resistance and not secondary to the effect of ACh on cardiac muscarinic receptors. Similar doses of ACh lower MAP in rabbits, rats, and humans (8,16,27). These dose-dependent decreases in MAP after ACh are also unrelated to the basal MAP, as previously reported in rats and rabbits (8,18,35).…”
Section: Discussionsupporting
confidence: 60%
“…Thus this decrease in MAP results from decreased vascular resistance and not secondary to the effect of ACh on cardiac muscarinic receptors. Similar doses of ACh lower MAP in rabbits, rats, and humans (8,16,27). These dose-dependent decreases in MAP after ACh are also unrelated to the basal MAP, as previously reported in rats and rabbits (8,18,35).…”
Section: Discussionsupporting
confidence: 60%
“…As we have found previously (16,17,21,34,35), responses to RNS were highly reproducible across the course of the experiment in control rabbits (group 1). By analyzing our results mainly in a within-animal fashion, we were able to detect relatively modest effects of ANG II and PD123319 on responses to RNS, even though responses to RNS can vary somewhat in different rabbits.…”
Section: Discussionsupporting
confidence: 51%
“…We have indirect evidence that this effect is mediated by NO, since 1) NO synthase (NOS) blockade enhances responses of MLDF to RNS (16,34,35), and 2) under conditions of NOS blockade renal arterial infusion of ANG II enhances responses of MLDF to RNS (35). Our current observations suggest that the effects of exogenous ANG II on neural control of medullary blood flow are mediated by AT 2 receptors, since they were abolished by PD123319.…”
Section: Discussionmentioning
confidence: 67%
“…27 A reduction in renal NO bioavailability can increase the responsiveness of the kidney to any given level of renal sympathetic nerve activity (RSNA). For example, we and others have shown that reduced renal NO levels can induce greater reductions in renal medullary perfusion to a given level of RSNA, 29,30 which in turn can lead to sodium and water retention leading to hypertension. 31 Indeed, in fat fed rabbits, stimulation of renal nerves resulted in greater reductions in medullary perfusion and sodium retention when compared with controls.…”
Section: Reduced No Bioavailability Can Exacerbate the Prohypertensivmentioning
confidence: 92%
“…27 La disminución de la biodisponibilidad de NO renal puede aumentar la capacidad de respuesta del riñón a determinado nivel de actividad nerviosa simpática renal (ANSR). Por ejemplo, nosotros y otros colegas hemos demostrado que la disminución del nivel de NO renal puede inducir una mayor reducción de la perfusión en la médula renal a determinado nivel de ANSR, 29,30 lo que a su vez puede derivar en la retención de sodio y agua y terminar en hipertensión. 31 De hecho, en conejos con una dieta a base de grasas, la estimulación de los nervios renales dio como resultado mayor reducción de la perfusión en la médula renal y retención de sodio en comparación con los controles.…”
Section: -24unclassified